Multi-objective management in freight logistics : increasing capacity, service level, sustainability, and safety with optimization algorithms /: increasing capacity, service level, sustainability, and safety with optimization algorithms. ([2020]) - Caramia, Massimiliano; Dell'Olmo, Paolo, 1958-
No abstract available